The Root of Violence in Kanjuruhan Tragedy - Jenny Yudha Utama; Erna Anggraeni; Erni Erviani; Hendra Prabowo; Vitroh Wahyu Saputra (Department of Political Science - Universitas Sains Al-Qur’an, 2022)
The Kanjuruhan tragedy is the biggest football tragedy in Indonesia, even the second largest after similar catastrophe in Peru in 1964. The highlight of this tragedy was the shooting of tear gas by the police. This is certainly Contrary to the regulations of the Federation Internationale de Football Association (FIFA), that firearms and tear gas cannot be used for crowd control. The purpose of this study is to review academically the roots of violence for evaluation for Indonesian Police Institutions to be better and such tragedy will not happen again in the future. This study employes Erich Fromm's theory to solve the roots of violence. The method used a qualitative method with a case study approach with data collection techniques of observation, interviews, and documentation in Kanjuruhan, Malang. The results obtained by the researchers are that the Kanjuruhan tragedy is classified as destructive violence, this is because many casualties in the tragedy were caused by panic and less conducive conditions. In connection with this, the National Police institution must implement proper regulations.